The Repetitive DNA Composition in the Natural Pesticide Producer Tanacetum cinerariifolium: Interindividual Variation of Subtelomeric Tandem Repeats - Mlinarec, Jelena (Front Plant Sci, 2019)
Dalmatian pyrethrum (Tanacetum cinerariifolium (Trevir.) Sch. Bip.), a plant species endemic to the east Adriatic coast, is used worldwide for production of the organic insecticide, pyrethrin. Most studies concerning Dalmatian pyrethrum have focused on its morphological and biochemical traits relevant for breeding. However, little is known about the chromosomal evolution and genome organization of this species. Our study aims are to identify, classify, and characterize repetitive DNA in the T. cinerariifolium genome using clustering analysis of a low coverage genomic dataset. Repetitive DNA represents about 71.63% of the genome. T. cinerariifolium exhibits linked 5S and 35S rDNA configuration (L-type). FISH reveals amplification of interstitial telomeric repeats (ITRs) in T. cinerariifolium. Of the three newly identified satellite DNA families, TcSAT1 and TcSAT2 are located subterminally on most of T. cinerariifolium chromosomes, while TcSAT3 family is located intercalary within the longer arm of two chromosome pairs. FISH reveals high levels of polymorphism of the TcSAT1 and TcSAT2 sites by comparative screening of 28 individuals. TcSAT2 is more variable than TcSAT1 regarding the number and position of FISH signals. Altogether, our data highlights the dynamic nature of DNA sequences associated with subtelomeres in T. cinerariifolium and suggests that subtelomeres represent one of the most dynamic and rapidly evolving regions in eukaryotic genomes.